Dose-Related Modulation of Event-Related Potentials to Novel and Target Stimuli by Intravenous Δ(9)-THC in Humans - D'Souza, Deepak Cyril (Nature Publishing Group, 2012)
Cannabinoids induce a host of perceptual alterations and cognitive deficits in humans. However, the neural correlates of these deficits have remained elusive. The current study examined the acute, dose-related effects of delta-9-tetrahydrocannabinol (Δ(9)-THC) on psychophysiological indices of information processing in humans. Healthy subjects (n=26) completed three test days during which they received intravenous Δ(9)-THC (placebo, 0.015 and 0.03 mg/kg) in a within-subject, double-blind, randomized, cross-over, and counterbalanced design. Psychophysiological data (electroencephalography) were collected before and after drug administration while subjects engaged in an event-related potential (ERP) task known to be a valid index of attention and cognition (a three-stimulus auditory ‘oddball' P300 task). Δ(9)-THC dose-dependently reduced the amplitude of both the target P300b and the novelty P300a. Δ(9)-THC did not have any effect on the latency of either the P300a or P300b, or on early sensory-evoked ERP components preceding the P300 (the N100). Concomitantly, Δ(9)-THC induced psychotomimetic effects, perceptual alterations, and subjective ‘high' in a dose-dependent manner. Δ(9)-THC -induced reductions in P3b amplitude correlated with Δ(9)-THC-induced perceptual alterations. Lastly, exploratory analyses examining cannabis use status showed that whereas recent cannabis users had blunted behavioral effects to Δ(9)-THC, there were no dose-related effects of Δ(9)-THC on P300a/b amplitude between cannabis-free and recent cannabis users. Overall, these data suggest that at doses that produce behavioral and subjective effects consistent with the known properties of cannabis, Δ(9)-THC reduced P300a and P300b amplitudes without altering the latency of these ERPs. Cannabinoid agonists may therefore disrupt cortical processes responsible for context updating and the automatic orientation of attention, while leaving processing speed and earlier sensory ERP components intact. Collectively, the findings suggest that CB1R systems modulate top-down and bottom-up processing.